2017
DOI: 10.1007/s40429-017-0177-4
|View full text |Cite
|
Sign up to set email alerts
|

Exercise as a Sex-Specific Treatment for Substance Use Disorder

Abstract: Purpose of Review Exercise is a promising treatment for substance use disorder that may reduce withdrawal symptoms and prevent relapse. In this review, we discuss recent evidence from clinical and preclinical studies for its efficacy, from a behavioral to a molecular level, in order to understand the exercise conditions that lead to beneficial effects. We also highlight the few recent findings of sex-specific differences. Recent Findings Clinical and preclinical findings show that exercise decreases withdraw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 94 publications
1
8
0
Order By: Relevance
“…Rather, it appears that drug-and cue-primed reinstatement functioned as an establishing operation (Michael 1982) that increased the reinforcing efficacy of wheel running in female rats. Collectively, the results of the present study add to a growing body of literature on exercise as an effective treatment for drug abuse (e.g., Zlebnik et al 2010;Lynch et al 2017). For human drug abusers, these results suggest a benefit of voluntary physical activity to reduce drug-seeking and increase the likelihood of an individual to engage in physical activity instead of relapsing into drug abuse.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Rather, it appears that drug-and cue-primed reinstatement functioned as an establishing operation (Michael 1982) that increased the reinforcing efficacy of wheel running in female rats. Collectively, the results of the present study add to a growing body of literature on exercise as an effective treatment for drug abuse (e.g., Zlebnik et al 2010;Lynch et al 2017). For human drug abusers, these results suggest a benefit of voluntary physical activity to reduce drug-seeking and increase the likelihood of an individual to engage in physical activity instead of relapsing into drug abuse.…”
Section: Discussionsupporting
confidence: 68%
“…In the present study, there was no relationship between the change in active lever responses from the control to priming session and the number of wheel revolutions during the priming session in either sex. This lack of concordance has also been found in the past by several other studies that employed either inor out-of-session wheel access and all reported a lack of correlation between wheel revolutions and drug-seeking behavior (Smith and Pitts 2012;Zlebnik et al 2014a;Zlebnik and Carroll 2015b; see review by Lynch et al 2017). One potential explanation is that the time spent in the running wheel is a better predictor of the treatment effects rather than the intensity (i.e., revolutions/min).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Exercise shows promise as a non-pharmacological intervention for addiction in both humans and animal models (Lynch et al 2017;Wang et al 2014a). In humans, exercise during abstinence reduces craving for cocaine and other drugs of abuse (Abrantes et al 2011;Wang et al 2014a), and recent findings provide preliminary support for its ability to reduce relapse (De La Garza et al 2016;Trivedi et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These results have motivated to develop more studies in polysubstance users, however such studies are currently in conduction (Ellingsen, Johannesen, Martinsen, Dahl, & Hallgren, 2020). In addition to these studies, preclinical evidence suggest that participant characteristics such as age and gender could be associated with the positive results of exercise in craving (Lynch, Abel, Robinson, & Smith, 2017).…”
Section: Introductionmentioning
confidence: 99%